Methyl-α-D-glucopyranoside from Tulbaghia violacea extract induces apoptosis in vitro in cancer cells (Bangladesh Journal of Pharmacology, 2013)
Pro-apoptotic activity of Tulbghia violacea extracts was evaluated in order to understand the mechanisms of action that might be related to its traditional use as anticancer medicine. Apoptosis-guided purification was used to isolate active compound whose chemical structure was solved by using spectros-copic, microanalysis and X-ray crystallography techniques. T. violacea extract kills Chinese hamster ovary cells, MCF7, and HeLa cells through the induction of apoptosis Methyl-a-D-glucopyranoside was identified as one of the main pro-apoptotic compounds present in T. violacea extract. This is the first time ever demonstration that T. violacea contains methyl-a-D-glucopyranoside, which selectively kills cancer cells through apoptosis mechanisms.